PENERAPAN GAME EDUCATION CAPLAY UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI PADA MATERI EKOSISTEM KELAS 7 SMP NEGERI 1 FAKFAK - Diyani Diyani; Ratna Prabawati; Jaharudin Jaharudin (CV. ADIBA AISHA AMIRA, 2025)
The interest in learning among students at SMP Negeri 1 Fakfak is still low, which can lead to inactive learning and negatively impact learning outcomes. Therefore, as educators, we must be able to stimulate students' interest in learning. We, as educators, must also be able to increase interest in learning, which is the most important thing in every human being in order to achieve the goals set by an educator, especially in students to have enthusiasm in learning. A good educator is able to stimulate interest in learning. However, each subject has a different level of difficulty, so to stimulate interest in learning, there must be strong encouragement, especially from educators. The research question in this study is: How can the application of Caplay Educational Games improve learning outcomes in biology on the topic of ecosystems in Grade 7 at SMP Negeri 1 Fakfak? This study uses a quantitative research method. The population in this study is Grade 7B students. The sampling techniques used in this study are learning outcome tests, observations, interviews, and documentation. The objective of this study is: How to apply the Caplay Educational Game to improve biology learning outcomes on the ecosystem topic in Grade 7 at SMP Negeri 1 Fakfak for the 2024/2025 academic year, aiming to achieve a minimum passing grade of 70 as set by the school. The application of Game Education Caplay can be used to help students understand lesson concepts and practice questions that are designed to be engaging and adapted to technological advancements. Additionally, it can stimulate students' creativity and enhance their logical thinking and understanding when using it. Currently, many students are more interested in using computers or other technological media.